Is China's potential slowdown growth a threat to the global economy of Europe and the US? - Palla, Martin; Ruschka, Adam; Slaný, Martin, 1982-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
The aim of this thesis is to determine whether a slowdown in Chinese growth will have a negative impact on the economies of the European Union and the United States. In the theoretical part, I utilize concepts from Robert Solow's economic growth model, and in the practical part, I apply a model based on Vector Autoregression (VAR). The focus is on analysing the impulse response functions after a shock to GDP of each individual country. The analysis also includes usage of exogenous variables and variance decomposition. The results show that the Chinese economy significantly influences the economies of the EU and the USA, suggesting that a slowdown in China's economy is likely to have adverse effects on the economies of the EU and the USA as well.
Vedoucí práce: Adam Ruschka
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: ekonomie [obor bakal. práce]; bakalářské práce; bachelor's theses